The beekeeper of Sinjar : rescuing the stolen women of Iraq / (Acc. D2123) - Mikhail, Dunya (USA : Serpent's Tail, 2019)
In The Beekeeper of Sinjar, the acclaimed poet and journalist Dunya Mikhail tells the harrowing stories of women from across Iraq who have managed to escape the clutches of ISIS. Since 2014, ISIS has been persecuting the Yazidi people, killing or enslaving those who won't convert to Islam. These women have lost their families and loved ones, along with everything they've ever known. Dunya Mikhail weaves together the women's tales of endurance and near-impossible escape with the story of her own exile and her dreams for the future of Iraq. In the midst of ISIS's reign of terror and hatred, an unlikely hero has emerged: the Beekeeper. Once a trader selling his mountain honey across the region, when ISIS came to Sinjar he turned his knowledge of the local terrain to another, more dangerous use. Along with a secret network of transporters, helpers, and former bootleggers, Abdullah Shrem smuggles brutalised Yazidi women to safety through the war-torn landscapes of Iraq, Syria, and Western Turkey. This powerful work of literary nonfiction offers a counterpoint to ISIS's genocidal extremism: hope, as ordinary people risk torture and death to save the lives of others.